2014
DOI: 10.1521/psyc.2014.77.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Subjective Olfaction Across the Schizophrenia Spectrum

Abstract: Much research indicates that patients with schizophrenia have impaired olfaction detection ability. However, studies of individuals with psychometrically defined schizotypy reveal mixed results-some document impairments while others do not. In addition to deficits in objective accuracy in olfaction for patients with schizophrenia, there has been an interest in subjective experience of olfaction. Unfortunately, methods of assessing accuracy and subjective hedonic olfactory evaluations in prior studies may not h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…The notion that satisfaction reflects a stable “set point” that is, in large part, heritable (Lykken and Tellegen, 1996) is interesting in that schizotypal features are largely stable (Chapman et al, 1994) and, at least to some degree, heritable (Docherty and Sponheim, 2008; MacDonald et al, 2001). In this regard, subjective dissatisfaction, whether it be in QOL, cognitive concerns (Chun et al, In Press) or in response to laboratory stimuli (Auster et al, 2013; Cohen et al, 2012a), may reflect stable trait features, and perhaps more importantly, a marker of illness vulnerability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The notion that satisfaction reflects a stable “set point” that is, in large part, heritable (Lykken and Tellegen, 1996) is interesting in that schizotypal features are largely stable (Chapman et al, 1994) and, at least to some degree, heritable (Docherty and Sponheim, 2008; MacDonald et al, 2001). In this regard, subjective dissatisfaction, whether it be in QOL, cognitive concerns (Chun et al, In Press) or in response to laboratory stimuli (Auster et al, 2013; Cohen et al, 2012a), may reflect stable trait features, and perhaps more importantly, a marker of illness vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there appears to be discrepancy between subjective and objective emotion functioning in college schizotypy. Third, a dysjunction has been reported in olfactory functions (Auster et al, 2013). In this study, college individuals with schizotypy reported lower levels of subjective pleasure when rating a range of olfaction stimuli compared to both patients with schizophrenia and college controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the negative symptoms which characterize this illness have been related to the dysfunction in olfactory accuracy [193]. Nevertheless, there are controversial reports describing an alteration in the sense of smell in schizophreniaassociated disorders [190,194] and others showing the absence of olfactory changes between psychotic patients and healthy controls [193,195,196]. Starting from this discrepancy, Auster and colleagues addressed whether the presence of olfactory deficits could represent a reliable marker for subjects potentially susceptible to develop schizophrenia.…”
Section: Schizophrenia and Autismmentioning
confidence: 99%
“…Starting from this discrepancy, Auster and colleagues addressed whether the presence of olfactory deficits could represent a reliable marker for subjects potentially susceptible to develop schizophrenia. They investigated this aspect comparing the smell functionality in four different groups: (1) schizophrenic individuals, (2) persons with different mental disorders than schizophrenia, (3) subjects affected by schizotypy and (4) healthy controls [193]. To achieve their goal, they modified a common olfaction test, the "Sniffin' Sticks" [193,197], in order to expand its efficiency for free recall tests in addition to olfaction ability and discrimination.…”
Section: Schizophrenia and Autismmentioning
confidence: 99%